Synthesis of Pyrimidine and Piperazine Based Medicinal Compounds - Ramani K. Kawadkar, Ms.; Ghiya, B.J. (Asian Journal of Chemistry, 2010)
2-Amino pyrimidines on condensation with piperazine in presence offormaldehyde in acidic alcohol leads to the formation of 1,4-di[2-aminodiaryl pyrimidine] 1,4-dimethyl piperazine. All the compounds werepurified and analysed using physical and chemical methods and werefurther confirmed by spectral studies. The antibacterial effect was studiedby using the cup-plate (N. agar) technique on four different strains ofbacteria. The synthesised compounds were further studied for the evaluationof anti-AIDS, anticancer and antileprosy activities also.